Antimicrobial resistance: Optimizing antimicrobial use in food-producing animals - Viviana Munoz Tellez (South Centre, 2024)
The increasing resistance of microorganisms to antimicrobials that help to treat and control spread of infections is a major public health problem around the world. Antimicrobial resistance is aggravated by inappropriate use of antimicrobials in human and animal health and in plant and animal agriculture. This paper tackles the question of how to shift animal food production to implement adequate antimicrobial stewardship practices.
Keywords: 300; Agriculture; Animal Health; Antibiotics; Antimicrobial Resistance (AMR); Antimicrobial Stewardship; Antimicrobials; Environmental Health; Fair Trade; Food Animal Production; Food Production; Food Safety; Food Security; Health; Human Health; Livestock Producers; Public Health; Sustainability; Viviana Munoz Tellez